Documentación IV. United Kingdom & Gibraltar - Communications and press releases (2024-2025) - Bellido Lora, María de los Ángeles; Del Álamo Marchena, Enrique (Cuadernos de Gibraltar – Gibraltar Reports, 2025)
Documentación incluida en este apartado: DOCUMENTO 1. Progress of UK-EU agreement in respect of Gibraltar: Joint statement, 19 September 2024. DOCUMENTO 2. Agreement protects sovereignty and economic security of Gibraltar: 11 June 2025. DOCUMENTO 3. Top level treaty meeting in Brussels 253/2024: 10 April 2024. DOCUMENTO 4. UK and Gibraltar Ministers discuss Treaty work and contingency planning - 303/2024: 2 May 2024. DOCUMENTO 5. Joint Statement on High Level Meeting in Brussels - 348/2024: 16 May 2024. DOCUMENTO 6. Unauthorized Guardia Civil Vessel Activity within British Gibraltar Territorial Waters - 467/2024: 27 June 2024. DOCUMENTO 7. Treaty discussions with new Foreign Secretary - 579/2024: 04 September 2024. DOCUMENTO 8. Chief Minister visits La Linea - 849/2024: 19 December 2024. DOCUMENTO 9. Chief Minister meets Minister for Europe - 24/2025: 13 January 2025. DOCUMENTO 10. HM Government of Gibraltar Welcomes European Commission’s Proposal to Remove Gibraltar from EU AML List - 431/2025: 10 June 2025. DOCUMENTO 11. UK-EU Gibraltar Trade and Mobility Agreement - 434/2025: 11 June 2025. DOCUMENTO 12. Chief Minister’s address to the Committee of 24 the United Nations - 450/2025: 18 June 2025. DOCUMENTO 13. CM Statement to Parliament on the treaty - 465/2025: 23 June 2025. DOCUMENTO 14. Gibraltar Officially Removed from EU High-Risk Third Country List - 573/2025: 05 august 2025. DOCUMENTO 15. HM Government of Gibraltar Welcomes Historic Gathering of All Living Chief Ministers at Campo de Gibraltar Commemoration - 695/2025: 26 September 2025.